Не Борисовы камни: о древнерусских надписях на станковом кресте, Воротишином камне и Друйском камне - Михеев, Савва Михайлович (Slavia Orientalis, 2026)
The article focuses on three works of Rus lapidary epigraphy from the lands of ancient Polotsk. Consulting old publications on a short inscription made on a stone cross from Ksty, near Polotsk, led the author to read it and make an assumption about its dating. The production of a 3D model by the RSSDA Lab made it possible to read the full inscription on the boulder from Vileika District, Minsk Region, known as ‘Vorotisha’s Stone’. The inscription on the boulder from Braslav District, Vitebsk Region, or the so-called Druia Stone, has come down to us in fragmented form. Previously, only the standard formula in the left half of the inscription had been identified. New photographs have allowed the author to read most of the right half of the inscription, with some uncertain areas. Taken together, the inscriptions on all three monuments, as well as on the other Dvina Stones (including Sulibor’s Stone, Boris’ four stones, all from the vicinity of Polotsk, and the Rogvolod’s Stone from near Orsha), record either the name of the commissioner or two of his names: secular and baptismal. In the case of the cross from Ksty, or the ‘Stanko’s Cross’, it may refer not to the commissioner, but to a deceased person, in whose memory the cross was erected. The text of the Druia inscription may also contain the name of the stone carver.